Exosome-based immunotherapies in ovarian cancer development of preclinical models and therapeutics - SIMONE PISANO (2021)
Treatment of ovarian cancer (OC) continues to present clinical challenges. It remains difficult to diagnose early stage disease, and because of this generally presents as advanced stage, with limited therapeutic options and often the development of resistance to chemotherapy. Furthermore, OC is considered as an immunologically “cold” tumour based on the poor response to immunotherapies. This lack of response to immunotherapy remains poorly understood, hence better models are needed in order to elucidate the fundamental mechanisms behind tumour immunosuppression, and for new and innovative therapeutic strategies to be tested. Exosomes have recently emerged as crucial players in the cell-cell communication and content exchange within the tumour microenvironment and have also been investigated for their capacity to act as cancer therapeutics or to be re-engineered to increase their performances and effects. In this work, two main research areas were explored. The first one focused on advanced ovarian cancer modelling. Indeed, the in vitro formation of multicellular spheroids that included a mixture of cancer cells and different macrophage phenotypes was optimised, and their characteristics explored. Additionally, an in vivo advanced OC model was created from immunocompetent mice and the tumours were characterised for their immune infiltrates presence. The ascitic fluid that arose from the tumour-bearing mice was also comprehensively analysed for its immune cells content by mass cytometry for the first time in an ovarian cancer setting. The second part of the work involved the exploration of two innovative OC therapeutics. Dendritic-cell (DC) derived exosomes were obtained from tumour antigen-pulsed DCs and tested for their efficacy both in vitro and in vivo. A semi-synthetic exosomes approach was also tested by forcing monocytic cells through pores of different sizes and obtaining Immune (Cell) Derived Exosome Mimetics (IDEM). IDEM were characterised and tested in vitro on both 2D and spheroid systems.